Nonalcoholic Fatty Liver Disease: Pathologic Patterns and Biopsy Evaluation in Clinical Research - Kleiner, David E.; Brunt, Elizabeth M. (Seminars in Liver Disease, 2012)
Nonalcoholic fatty liver disease (NAFLD) results in histologically complex specific and nonspecific injury patterns. In clinical research of NAFLD, the liver biopsy evaluation provides a wealth of information on the architectural arrangement and severity of a variety of histologic changes, including steatosis, inflammation, cellular injury, and fibrosis. This information is summarized as an overall diagnostic category, such steatosis or steatohepatitis and the severity of the injury can be graded and staged. Histopathologic disease classification in NAFLD is related to but separate from evaluation of individual histologic lesions. The patient population under study may affect the prevalence of histologic findings and in particular, pediatric patients with NAFLD may show a higher prevalence of zone 1 steatosis and periportal fibrosis as compared with adult populations. For the purposes of clinical research, it is important to provide the pathologist with biopsies that are adequate to classify the disease process as well as to grade and stage the changes. A current understanding of NAFLD pathologic classification, as well as nuances of grading and staging, is presented in this review.
Keywords: Bariatric surgery; disease classification; lipodystrophy; liver biopsy; nonalcoholic fatty liver disease; pediatric fatty liver disease; steatohepatitis; steatosis